Development of Chemistry Teaching Materials: Boundless Creativity in Transforming Recycled Materials into Innovative 3D Atomic Models - Marfu’ah, Siti; Yufika, Dona; Siregar, Keysha K.; Rani, Rani; Wulan, Tri; Rispa, Rispa; Agustina, Reni (Proceeding International Conference on Religion, Science and Education, 2025)
Chemistry education, particularly in teaching atomic concepts, often faces challenges in visualizing abstract ideas. This study aims to develop three-dimensional atomic models using recycled materials to represent the theories of Dalton, Thomson, Rutherford, and Bohr, while also exploring the potential integration of environmental education within chemistry learning. This research employs an exploratory approach through prototype development, involving six chemistry education students and one instructor. The development process consists of three stages: preparation (literature review and materials collection), prototype development (construction of four atomic models), and evaluation (internal assessment and refinement). The study resulted in four distinct three-dimensional atomic models: Dalton’s model uses a 15 cm black plastic ball, Thomson’s model incorporates a blue ball with red electrons, Rutherford’s model features a wire system with 17 electron caps, and Bohr’s model combines styrofoam and aluminum wire to visualize layered orbitals. Analysis indicates that recycled materials can be effectively utilized to create both informative and aesthetically appealing teaching media, while also supporting sustainability principles in education. The main challenge lies in balancing representational accuracy with material limitations, yet this can be addressed through creative material selection and processing. This study contributes to the development of affordable and eco-friendly chemistry learning media, promoting the integration of sustainability values in science education.